Photodegradation of lauth's violet dye using GO-Fe3O4-TiO2 nanocomposite under solar light. Issue 1 (March 2021) - Hashim, A; Al-Abodi, E E
Abstract: TFGO nanocomposite was synthesized from limited amounts of Titanium dioxide nanoparticles and Iron oxide nanoparticles as well as Graphene oxide nanosheets, by a situ method preparation. The producting materials were identify by (FTIR) and (AFM). The photocatalysis activity of TFGO nanocomposite was investigated by applying it in advanced oxidation processes (AOP) to degradation of Lauth's violet or Thionine acetate (LV) dye under solar light. The photodegradation efficiency of LV dye could be gained 98% at existance of TFGO nanocomposite as photocatalyst within 320 min. Photocatalytic processes experiments were happen at different effects like temperatures and existence of light.